2016
DOI: 10.1039/c5ob02138c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anti-tubercular activity of N2-arylbenzo[g]isoquinoline-5,10-dione-3-iminium bromides

Abstract: Tuberculosis has remained a challenge for medicinal chemists worldwide. In the framework of a collaborative program to identify and evaluate novel antitubercular candidate compounds, the biological properties of benzo[g]isoquinoline-5,10-diones have been found to be very promising. In this paper we have further expanded the library by incorporation of an amidinium moiety into the benzo[g]isoquinoline-5,10-dione scaffold. The presence of this functional group also increased the solubility of the quinones in pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…As shown in antitubercular activity in comparison to their structural analogs 4. 8 In case of the diarylated analogs 30a and 30b, antitubercular activity again abolished completely (MIC > 64 µM). Finally, possible genotoxicity of the analogs and their potential metabolites was investigated using a Vitotox TM assay.…”
Section: Biologymentioning
confidence: 95%
See 1 more Smart Citation
“…As shown in antitubercular activity in comparison to their structural analogs 4. 8 In case of the diarylated analogs 30a and 30b, antitubercular activity again abolished completely (MIC > 64 µM). Finally, possible genotoxicity of the analogs and their potential metabolites was investigated using a Vitotox TM assay.…”
Section: Biologymentioning
confidence: 95%
“…It is believed that the "out of plane" nature of these compounds contribute to a lower cytotoxity than their corresponding unsaturated analogs 7 . In our last publication 8 we have explored the effects of incorporating an amidine functional group into the C-ring (Figure 1) of the benzo[g]isoquinoline-5,10-dione core on solubility in polar solvents and the activity against Mtb. Improved solubility and nano-molar anti-mycobacterial activity of these compounds 4 proves the merit of core structure 5 as a template towards new antibiotics, notably for antitubercular compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular location of isoquinoline is in the cytoplasm [46]. Isoquinoline and its derivatives have been widely used as therapeutic agents for atherosclerosis therapy [47] and antibacterial [48], antituberculosis [49], anticancer [50], and antimalarial [51,52] agents, and others.…”
Section: Lc/ms Analysismentioning
confidence: 99%
“…From the biological evaluation, it can be concluded that the N 2 ‐arylbenzo [ g ]isoquinoline‐5,10‐dione‐3‐iminium bromides 9a – j (Fig. ) were much more active against MTB H37Rv than their dimethoxylated precursors 10a – j , and some of them were selected for further evaluation for their susceptibility against MDR‐TB and intracellular replicating MTB strains . The SAR revealed that derivatives bearing a halogen substituent on the phenyl ring showed an improved selectivity index compared with the derivatives with alternative substituents.…”
Section: Quinoline‐based Derivativesmentioning
confidence: 99%